Pendekatan Bisnis Model Canva dalam Analisis Strategi Pengembangan Usaha UMK KeriptaL Kota Bengkulu - Yesi Indian Ariska; Nirta Vera Yustanti; Desti Rupita Sari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to provide an overview of Canva's business model and provide a business transformation model for UMK KriptaL. This research was conducted at UMK KriptaL in Bengkulu City with its main production activity being the production of Taro Chips. This study uses a descriptive method with a qualitative approach, namely explaining and providing a more in-depth description of the situation and process for developing a cryptic MSE business. The main respondents in this research were UMK Kriptal business actors and employees by collecting data through in-depth interviews. The results of the study show that the UMK Kriptal business transformation model is a strategy that can be carried out to develop a business that will be obtained by maintaining the current Consumer Segments (CS) and Key Resources (Key Resources / KY). Things to add in the development of Kriptal UMK, namely on the Benefits Offered (Value Proposition/VP) by adding a website and social media promotions to the Customer Development block (Customer Relationship/CR).UMK Kriptal obtain Revenue Streams (Revenue Steams/RS) if there is innovation in the form of product sales new for example mocaf flour As well as maintaining existing collaborations and trying to add new collaborations for example cooperation with expedition services so that shipping costs can be cheaper on Partnerships (Key Partners).